ESTIMASI BADAI GEOMAGNET BERDASARKAN PERILAKU PARAMETER ANGIN SURYA DAN MEDAN MAGNET ANTARPLANET SEBELUM BADAI GEOMAGNET (THE ESTIMATION OF GEOMAGNETIC STORM BASED ON SOLAR WIND PARAMETERS AND INTERPLANETARY MAGNETIC FIELD BEHAVIOR BEFORE GEOMAGNETIC STOR - Anwar Santoso; Mamat Rahimat; Rasdewita Kesumaningrum; Siska Filawati (Jurnal Sains Dirgantara, 2016)
Space weather research is the principal activity at the Space Science Center, Lapan to learn characteristics and generator source of the space weather so that can mitigate its the impact on the Earth's environment as mandated in Law No. 21 Year 2013. One of them is the phenomenon of geomagnetic storms. Geomagnetic storms caused by the entry of solar wind together with the IMF Bz that leads to the south. The behavior of the solar wind parameters together with the IMF Bz before geomagnetic storms can determine the formation of geomagnetic storms that caused it. In spite that, by the solar wind parameters and IMF Bz behavior before geomagnetic storm can be estimated its intensity through the equation Dst * = 1.599 * Ptotal - 34.48. The result of this equation is obtained that the Dst minimum deviation between the raw data and the output of this equation to the geomagnetic storm events on March 17, 2013 is about of -2.51 nT or 1.9% and on the geomagnetic storm events on February 19, 2014 is about of 2.77 nT or 2, 5%. Thus, the equation Dst * = 1.599 * Ptotal - 34.48 is very good for the estimation of geomagnetic storms.